PENERAPAN KARAKTERISTIK MANAJEMEN RISIKO DALAM MEMINIMALISIR RISIKO KREDIT MACET PADA TOKO BAJU KREDIT RUMAHAN DI DESA ALASPANDAN - Putri Nur Afrida (Program Studi Ekonomi Syariah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2022)
There are several purposes in this article, the first aims to find out what are the factors that lead to bad credit at the Home Credit Clothing Store. The second aims to provide an overview of the application of risk management in minimizing the risk of bad clothes credit at Alaspandan Pakuniran Home Credit Clothing Stores. This article uses a qualitative approach research, because the research is based on the discovery of a social phenomenon or human problem that is currently happening. The study was conducted at the residence and location of the home credit clothing store business owner located in Alaspandan Pakuniran Village, Probolinggo Regency, East Java Province. The results show that if the character and business of the buyer of credit clothing is good, it will reduce the risk of bad credit. Therefore, in deciding the provision of clothing credit by the owner of the Home Credit Clothing Store, a more thorough analysis should be carried out.